The impacts of long-term changes in weather on small-scale fishers’ available fishing hours in Nosy Barren, Madagascar - Farquhar, Samantha; Nirindrainy, Avisoa Francis; Heck, Nadine; Saldarriaga, Maria Gomez; Xu, Yicheng (Frontiers in Marine Science, 2022)
Small-scale fisheries (SSF) are highly susceptible to changes in weather patterns. For example, in Nosy Barren, Madagascar, SSF use traditional pirogues with handcrafted sails that rely on seasonal wind and sea conditions. As climate change is expected to increase the intensity and frequency of severe weather, it is important to understand how changes in weather affect SSF fishing efforts. Yet, a gap exists in the understanding of how changes in meteorological conditions affect small scale fishers. This study combines fishers’ meteorological knowledge of weather conditions that allow for small-scale fishing with long-term remotely sensed meteorological data to quantify how fishing effort, defined as available fishing hours, of SSF in coastal Madagascar has changed between 1979-2020 in response to long-term weather trends. Results show a significant decrease in available fishing hours over the examined time period. Particularly, we found that a decrease in available fishing hours between 1979-2020 with a loss of 21.7 available fishing hours per year. Increased adverse weather conditions, likely associated with climate change, could decrease fishers access to crucial resources needed for the food and livelihood security. Climate change adaptation strategies will need to account for changing weather impacts on fishing availability.